2020
DOI: 10.3390/jcm9061606
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Interstitial Lung Disease Associated with Autoimmune Diseases: Data of a 3.6-Year Prospective Study from a Referral Center of Interstitial Lung Disease and Lung Transplantation †

Abstract: Interstitial lung disease (ILD) may occur in patients with a rheumatic autoimmune disease (AD), increasing their risk of morbidity and mortality. However, little is known about the prevalence of AD in patients diagnosed with an ILD. In this prospective study, we determined the spectrum of ILD associated with AD (AD-ILD) among patients sent for assessment to a single clinic of ILD and lung transplantation from a referral center between May 2016 and December 2019. ILD diagnosis was made by pneumologists based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…The inconsistent terminology and definitions across studies resulted in different prevalence data and reflect the absence of established diagnostic criteria [26]. In our study, the uILD cohort represented approximately 15% of the total ILD cohort, and approximately 26% of the IIP cohort, similar to the study by Atienza-Mateo et al [27]. The study by Ryerson et al reported a percentage of uILD of 10% of the ILD cohort [28].…”
Section: Discussionsupporting
confidence: 74%
“…The inconsistent terminology and definitions across studies resulted in different prevalence data and reflect the absence of established diagnostic criteria [26]. In our study, the uILD cohort represented approximately 15% of the total ILD cohort, and approximately 26% of the IIP cohort, similar to the study by Atienza-Mateo et al [27]. The study by Ryerson et al reported a percentage of uILD of 10% of the ILD cohort [28].…”
Section: Discussionsupporting
confidence: 74%
“…Although ILD frequently develops in patients with established RA, it may also be presented as the initial or single manifestation of an unidentified RA [ 1 , 2 , 3 ]. In this regard, the identification of an underlying RA in ILD patients remains a challenge, considering that RA-ILD + shares clinical, pathological, and epidemiological similarities with idiopathic pulmonary fibrosis (IPF), the most common and severe ILD [ 2 , 3 , 4 ]. Consequently, some patients initially defined as having IPF may be finally diagnosed with RA-ILD + [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in clinical practice, it is common to come across patients with an “idiopathic” interstitial pneumonia (IIP) associated with features suggestive of, but not diagnostic for, a classical CTD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%